EXPLORING CULTURAL ANTHROPOLOGY IN LIBYA: HERITAGE, IDENTITY, AND SOCIAL DYNAMICS - Riheel Alnaas Taha, Ayman; Salem Seed Gebreel, Omar (Penerbit Lafadz Jaya, 2024)
This study explores cultural anthropology in Libya by examining the diverse social practices, belief systems, and historical contexts that shape the Libyan identity. The research highlights the intersection of tradition and modernity, addressing the impact of political changes on cultural expressions. Through ethnographic methods, primary data from local communities, and a review of existing literature, this paper discusses the ongoing struggles and resilience of various ethnic groups, including Arab, Berber, and Tuareg populations. The significance of oral traditions, art, and communal rituals is analyzed to understand how culture acts as a vehicle for identity formation amid socio-political upheaval. The findings suggest that cultural anthropology provides critical insights into the complexities of Libyan society, fostering a deeper appreciation for its rich heritage while acknowledging the challenges posed by globalization and conflict. This article contributes to the broader field of cultural studies by elevating Libyan voices and narratives, thereby promoting a nuanced understanding of cultural identity in a transforming world.